A tailored molecular imprinting ratiometric fluorescent sensor based on red/blue carbon dots for ultrasensitive tetracycline detection - Liu, Xiqing; Wang, Tao; Wang, Wenjuan; Zhou, Zhiping; Yan, Yongsheng (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
Two kinds of well-resolved wavelengths carbon dots (CDs) including red-emission CDs (rCDs) and blue-emission CDs (bCDs) were fabricated using osmanthus fragrans leaves as carbon source through solvent extraction methods. The prepared bCDs as reference signal and rCDs as response signal were constructed the ratiometric fluorescence MIPs@rCDs@bCDs@SiO2 sensor by the precipitation polymerization process for ultrasensitive and high selective TC determination. [Display omitted] •The rCDs and bCDs were firstly fabricated using osmanthus fragrans leaves as carbon source by solvent extraction methods.•An environmental-friendly molecular imprinting ratiometric fluorescence sensor for detection of TC has been synthesized.•The MIPs@rCDs@bCDs@SiO2 was displayed ultrasensitive and excellent selective determination to tetracycline. The molecular imprinting ratiometric fluorescence sensor has exhibited great potential in biological and environmental detection because of the combination between the excellent selectivity of molecular imprinting technique and outstanding robustness of ratiometric measurement methods On this basis, two kinds of different well-resolved wavelengths and high-fluorescent carbon dots (CDs) were prepared by various solvent extraction using osmanthus fragrans leaves as carbon source. Then the ratiometric fluorescence sensor (MIPs@rCDs/bCDs@SiO2) has been constructed by the obtained CDs which the red-emission CDs (rCDs) were used to responsive signal and the blue-emission CDs (bCDs) was served as reference signal and applied for highly selective and excellent sensitive detection of tetracycline (TC). Under optimum conditions, the ratiometric fluorescence MIPs@rCDs/bCDs@SiO2 sensor has also exhibited lower detection limit of 1.19nM and the linear range of 0–50nM. The ratiometric fluorescence sensor was further successfully employed to the determination of TC in water samples gathered from local river water and tap water, indicating its great worth toward water sample analysis in complicated environments.